Thigmostimulation alters anatomical and biomechanical properties of bioenergy sorghum stems. (March 2022) - Zargar, Omid; Li, Qing; Nwaobi, Chiedu; Pharr, Matt; Finlayson, Scott A.; Muliana, Anastasia
Abstract: Sorghum [ Sorghum bicolor (L.) Moench ] is a tropical grass that can be used as a bioenergy crop but commonly suffers from stem structural failure (lodging) when exposed to mechanical stimuli, such as rain and wind. Mechanical stimulation can trigger adaptive growth in plant stems (thigmomorphogenesis) by activating regulatory networks of hormones, proteins, transcription factors, and targeted genes, which ultimately alters their physiology, morphology, and biomechanical properties. The goals of this study are 1) to investigate differences in the morpho-anatomical-biomechanical properties of internodes from control and mechanically-stimulated plants and 2) to examine whether the changes also depend on the plant developmental stages at the time of stimulation. The sweet sorghum cultivar Della was grown in a greenhouse under two growth conditions: with and without mechanical stimulation. The mechanical stimulation involved periodic bending of the stems in one direction during a seven-week growth period. At maturity, the anatomical traits of the stimulated and non-stimulated stems were characterized, including internode lengths and diameters, and biomechanical properties, including elastic (instantaneous) modulus, flexural stiffness, strength, and time-dependent compliance under bending. The morpho-anatomical and biomechanical characteristics of two internodes of the stems that were at different stages of development at the time of mechanical stimulation were examined. Younger internodes were more responsive and experienced more pronounced changes in length due to the stimulation when compared to the older internodes. Statistical analyses showed differences between the stimulated and non-stimulated stems in terms of both their anatomical and biomechanical properties. Mechanical stimulation produced shorter internodes with slightly larger diameters, as well as softer (more compliant) and stronger stems.